सा विद्या विमुक्तये ~That Is Knowledge Which Liberates!. Issue 1 (January 2019) - Tarapore, Homi
Abstract: Knowledge is the pursuit of the wise, and education is but a small step towards that knowledge. So when you see executive education, look at it like a weapon you need to acquire for your armoury as a professional. Executive education in India is still in its infancy and its potential is yet to be realized. As with most designs, it has started with being transitionally significant and will soon progress into being transformationally significant. With the dynamic shift in the work environment and the constant cycle of obsolescing and becoming relevant, a t-shaped person will be in constant need for up-skilling. In conclusion executive education is here to stay, it is a only a matter of how fast HR professionals and executive education experts crack the code of relevance and ROI.